TESTS AS TOOLS FOR ASSESSING STUDENTS’ PROGRESS - KHAMULIAK, Nataliia (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
This article defines the role of assessment in the learning process and its influence on students’ motivation. It also identifies the main types of tests, their purposes, test questions and their advantages, as well as characterizing the syllabus of the course “Foreign Language for Specific Purposes”.